Managing Domestic Violence Islamic Religious Perspective - Kamaruddin, Zaleha (Journal of Dharma, 2015)
Domestic violence is one of the most wide spread crimes in the contemporary society, irrespective of race, ethnicity, country, religion, and culture. The causes and reasons for domestic violence have been discussed quite extensively. The vindication of violence against women based on religious affiliation and a high rate of partner violence among particular religious communities has led social scientists to consider religion as a reason for violence in the family. In the case of Muslims, the verse 4:34 in the Qurān is identified as potentially influential. This has challenged the primary narrative of Islam as a religion that promotes peace and harmony. This article examines domestic violence in the context of religious teachings across cultures with special reference to Islam. The Malaysian experience in domestic violence found that confusion in interpreting the religious text with cultural affiliation contributes to domestic violence rather than the spirit of the religion itself. This paper proposes a contextual reading of texts to remedy such confusion - especially regarding verse 4:34 - while underlying socio-cultural and political conditions